Suhrawardi: A Philosopher Who Must Be Re-Known! - Niksirat, Abdollah (Journal of History Culture and Art Research, 2017)
In this article it has been dealt with the importance and place of Suhrawardi’s philosophical and illuminationist thoughts. His thought is the focal point in which the Zoroasterian, Platonic and peripatetic metaphysics and Islamic mysticism as well as the revelation and religious tradition have met together and have found new combination in one coherent system by his own innovations. The souvenir of Iranian ancient metaphysics is searched in the Iranian Sufism and mysticism; since the illuminationist philosophy is heavily influenced by the Iranian Sufism and mysticism, consequently one of the first-class sources is to know Eastern and Iranian mysticism. Through philosophical and mystical meditations Suhrawardi sought to close the truth of positive religion to the philosophical truth and in a word lump together the positive religion, mystical path and truth. His important preoccupation is to explain how the expatriate can return home; because the illuminationist philosopher is basically who does not separate the philosophical enquiry from the spiritual perfection.